Evidence for large diversity in the human transcriptome created by Alu RNA editing - Barak, Michal (Oxford University Press, 2009)
Adenosine-to-inosine (A-to-I) RNA editing alters the original genomic content of the human transcriptome and is essential for maintenance of normal life in mammals. A-to-I editing in Alu repeats is abundant in the human genome, with many thousands of expressed Alu sequences undergoing editing. Little is known so far about the contribution of Alu editing to transcriptome complexity. Transcripts derived from a single edited Alu sequence can be edited in multiple sites, and thus could theoretically generate a large number of different transcripts. Here we explored whether the combinatorial potential nature of edited Alu sequences is actually fulfilled in the human transcriptome. We analyzed datasets of editing sites and performed an analysis of a detailed transcript set of one edited Alu sequence. We found that editing appears at many more sites than detected by earlier genomic screens. To a large extent, editing of different sites within the same transcript is only weakly correlated. Thus, rather than finding a few versions of each transcript, a large number of edited variants arise, resulting in immense transcript diversity that eclipses alternative splicing as mechanism of transcriptome diversity, although with less impact on the proteome.